USING SOCIAL MEDIA PLATFORMS (TIKTOK, YOUTUBE, INSTAGRAM) TO IMPROVE ENGLISH SPEAKING SKILLS - Odilova Fotimakhon (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the pedagogical potential of social media platforms, specifically TikTok, Instagram, and YouTube, in developing English speaking skills. Unlike traditional methods, social media provides learners with exposure to "authentic language" and "shadowing" opportunities. The study analyzes how micro-learning through short-form videos contributes to fluency and phonetic accuracy. It evaluates the shift from formal classroom settings to autonomous digital learning environments and discusses the reduction of Foreign Language Speaking Anxiety (FLSA) through consistent digital interaction.